Evidence-Based Neuroimaging Diagnosis and Treatment Improving the Quality of Neuroimaging in Patient Care - Medina, L. Santiago; Sanelli, Pina C.; Jarvik, Jeffrey G. (Evidence-Based Imaging, Improving the Quality of Imaging in Patient Care, 2013)
Evidence-Based Neuroimaging is a user-friendly guide that employs evidence-based medicine criteria to systematically review the evidence defining the appropriate use of medical  imaging for the brain, spine, head, and neck. Edited by L. Santiago Medina, Pina C. Sanelli, and Jeffrey G. Jarvik, the book provides a systematic framework for understanding the best imaging choices for patient care. Chapters highlight key points that support clinical applications, allowing fast access to pertinent information including patient selection, imaging strategies, test performance, cost-effectiveness, and applicability. The diagnostic imaging of many common diseases, disorders, and conditions are covered, including multiple sclerosis, acute ischemic stroke, dementia, Alzheimer's disease, traumatic brain injury, autism, spinal trauma, spinal infections, neck masses, thyroid cancer, and cervical lymph node metastasis.  By offering a clear understanding of the science behind the evidence, the book fills a void for radiologists, neurologists, neurosurgeons, pediatricians, primary care physicians, and other clinicians with an interest in neuroimaging and a desire to implement an evidence-based approach into their daily practice.